The isolation of canine parvovirus and pathological changes of infected dogs - Sendow, Indrawati; Hamid, Helmy (Indonesian Journal of Animal and Veterinary Sciences, 2004)
The aims of this study are to isolate canine parvovirus (CPV) from the field case and to evaluate its histological aspects in CPV infected dogs. Samples were collected from intestine, intestine contained and mucose, as well as dogs feses from diarrhoea and blood diarrhoea. The suspension of those specimen was inoculated into Feline Kidney cells and observed for cythopathic effect (CPE). The presence of CPE indicated that there was viral isolate and continued to further identification using Haemaglutination (HA) test with pig red blood cells. Samples with positif in HA test were further identification using Haemaglutination Inhibition (HI) test against reference CPV antisera. Isolation result showed that from 81 samples processed, 10 samples indicated CPE in cell cultures, and had agglutinated in pig red blood cells and neutralised reference CPV antisera as the same titer of reference CPV antisera. Nine isolates were obtained from feces and 1 isolate was obtained from Mucose intestine from bloody diarrhoea dogs. Those isolates were also obtained from 1 to 2 days post blood diarrhea clinical signs. Two from 10 cadavers examined showed histological changes to CPV infection. Isolate of CPV, originally from feces, was also obtained from one of the two cadavers. Based on the results it was concluded that more CPV viral isolates can be obtained from bloody diarrhea feces. Â  Key words: Canine parvovirus, inhibition, isolation, pathology, identification